DETERMINATION OF HEAVY METAL CONCENTRATION IN DIFFERENT PARTS OF AZANZA GARKEANA PLANT AND THE CULTIVATED SOIL USING AAS TECHNIQUE - Abubakar, A. Y.; Nasiru, R.; Garba, N. N.; Lawal, A. U.; Kankara, U. M.; Ibrahim, N. (FUDMA Journal of Sciences, 2023)
Azanza garckeana is an edible fruit with medicinal values in the treatment of different ailments. The presence of Six Heavy metals (Cd, Co, Cr, Mn, Ni, and Pb) in different components of Azanza garckeana plant (seed, leaves, pulp and bark) and the cultivated soil, in part of Tula Kantungo LGA of Gombe State is investigated using atomic adsorption spectrometry (AAS). Digestion of the samples was carried out by mixing 2 g of each sample with solution of HCL and HNO3 in the ratio 2:1 and then heated at 100 oC for 1 hour. The concentration of the heavy metals in the seed, leaves, pulp, bark and soil are found to be in the range of 0.001- 0.791 ppm for Mn, 0.010-0.372 ppm for Co, 0.067-0.264 ppm for Cr, 0.006-0.237 ppm for Pb. 0.002-0.200 ppm for Ni, and 0.001-0.002 ppm for Cd. These values were compared with the recommended values set by World Health Organization (WHO) and Federal Environmental Protection Agency (FEPA)
Keywords: Medicinal plants, Gombe State, Toxic, Plants parts